DEVELOPMENT OF A GREEN ECONOMY IN THE REGIONS OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2026)
The article analyzes the theoretical foundations and practical features of the development of the regional economy based on the principles of the "green" economy. The influence of such factors as environmental sustainability, rational use of natural resources, the introduction of alternative energy sources on the socio-economic development of the regions is considered.